2016
DOI: 10.17221/126/2015-agricecon
|View full text |Cite
|
Sign up to set email alerts
|

Dairy farm profit according to the herd size, milk yield, and number of cows per worker

Abstract: Th e study evaluates the associations of the farm herd size (HERD), the milk yield (MY, kg/cow per year), and cows per worker (CW) with the production, reproduction, and economic traits in 60 commercial dairy herds (34 633 cows) in the Czech Republic. Each parameter was split into 3 groups. Th e largest herds (≥ 750 cows) had the highest profi tability of costs without subsidies (−3.8 ± 4.3%), the lowest cost for roughages (1.2 CZK/L milk), and the lowest cost for breeding operations (0.17 CZK/L milk), but the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…Herd size can also have an impact on milk production. Krpálková et al (2016) found that the highest milk producing herds (≥9000 kg/lactation) had the largest size (809.07±100.11 cows). Milk protein and milk fat content did not differ significantly by herd size.…”
Section: Introductionmentioning
confidence: 93%
“…Herd size can also have an impact on milk production. Krpálková et al (2016) found that the highest milk producing herds (≥9000 kg/lactation) had the largest size (809.07±100.11 cows). Milk protein and milk fat content did not differ significantly by herd size.…”
Section: Introductionmentioning
confidence: 93%
“…All the calculated costs based on the prevailing prices during the period of the study and were calculated on the basis of Egyptian pound (EGP). Total costs included total feed costs, labour costs, the miscellaneous costs, the costs for veterinary services and breeding operations, depreciation of fixed assets, cow depreciation costs according to, (Krpalkova et al, 2016).…”
Section: Variablesmentioning
confidence: 99%
“…Savickienė and Miceikienė [18] utilised the financial indicators to measure financial sustainability of Lithuanian farms. Krpalkova et al [19] and Naglova and Gurtler [20] concluded that Czech small farms were the least profitable farms, while the best results were achieved by large farms. Similarly, Poczta and Sredzińska [21] showed that Polish large farms were more profitable than small farms.…”
Section: Introductionmentioning
confidence: 99%